2019
DOI: 10.3390/w11122527
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance and Desalination Abilities of Nine Common Green Microalgae Isolates

Abstract: In recent years, decline of freshwater resources has been recognized as one of the main environmental problems on global level. In addition to the increasing extent of primary salinization due to climate change, secondary salinization caused by human interventions is also a significantly increasing problem, therefore, the development of various chemical-free, biological desalination and removal procedures will become increasingly important. In the present study, the salinity tolerance, salinity, and nutrient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 60 publications
3
26
0
Order By: Relevance
“…For instance, the growth of Chlorococcum sp. was only significantly inhibited in NaCl concentrations higher than 10 g L −1 [39]. Similarly, S. elongatus cells tolerate NaCl at concentrations up to 23.37 g L −1 (0.4 M) [40,41].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, the growth of Chlorococcum sp. was only significantly inhibited in NaCl concentrations higher than 10 g L −1 [39]. Similarly, S. elongatus cells tolerate NaCl at concentrations up to 23.37 g L −1 (0.4 M) [40,41].…”
Section: Discussionmentioning
confidence: 93%
“…Cell density and photosynthesis did not statistically change, even when cells were exposed to the highest NaCl concentration found in water of the Rio Doce Basin, demonstrating the salt-tolerance of S. elongatus and C. infusionum. Synechococcus elongatus and species of the genera Chlorococcum have been previously characterized as halotolerant and able to proliferate in environments with high salt concentrations [39,40]. For instance, the growth of Chlorococcum sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal N:P ratio for the treatment of municipal wastewater using microalgae is not well described. High nutrient concentrations with unfavorable N:P ratios could lead inadequate growth or nutrient removal: e.g., in our recent study all the tested nine green algae isolates showed poor phosphate removal from Bold's Basal Medium [20].…”
Section: Introductionmentioning
confidence: 84%
“…The experiments were carried out in model solutions with slightly different nitrate and phosphate concentrations and N:P ratios to represent how usual, not harsh fluctuations in wastewater composition could effect on biomass production and removal characteristics. On the basis of literature data and our previous findings [20] we hypothesized that:…”
Section: Introductionmentioning
confidence: 96%
“…Temperature was the sole exogenous factor chosen. Since C. vulgaris is also halotolerant with recognizable desalination ability [ 30 ], the impact of salinity was included by adding sodium chloride to mimic the conditions from freshwater to the marine environment.…”
Section: Methodsmentioning
confidence: 99%